Perceived learning and timely graduation for business undergraduates taking an online or hybrid course. Issue 6 (17th August 2016) - Blau, Gary; Drennan, Rob B.; Hochner, Arthur; Kapanjie, Darin
ABSTRACT: An online survey tested the impact of background, technological, and course-related variables on perceived learning and timely graduation for a complete data sample of 263 business undergraduates taking at least one online or hybrid course in the fall of 2015. Hierarchical regression results showed that course-related variables (instructor effectiveness, student motivation) were the most effective in explaining perceived learning, while perceived learning accounted for additional significant variance in explaining timely graduation.